Pengembangan Model Pembelajaran ARCS (Attention, Relevance, Confidence, Satisfaction) Dengan Wolfram Mathematica - Farida, Anisatul; Indah, Ratna Puspita (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2019)
AbstractThis study aimed to develop a computer-based ARCS kind of classroom that valid, practical, and effective.This research adopting both qualitative and quantitative research and development with a method developed by Gall and the Borg. This research subject was students of engineering information Duta Bangsa Universityperiod 2018 / 2019.An instrument in this research consists of ( 1 ) an instrument assessment valid components model and devices supporting learning, ( 2 ) an instrument assessment practicality of faculty and students, and ( 3 ) instrument effectiveness of which includes sheets of the test results learning and chief appreciation students to learning linear algebra computer-based.The subject of this research is 25 students who took linear algebra.  The study showed that Kind of classroom computer-based ARCS that met the criteria of valid, practical, and effective. Practicality ARCS kind of classroom computer-based based on ( 1 ) assessments from he got from his lecturers have reached very practical criteria; ( 2 ) assessing the from students we have achieved very practical criteria. The current effectiveness of ARCS kind of classroom computer-based based on ( 1 ) the results of  THB students, fulfilled the criteria the current effectiveness of with the percentage 76 %, ( b ) appreciation students learning ARCS against computer-driven which reached the criteria for good. It is also can be said that there is a correlation between appreciation students learning arcs against computer-based learning about mathematics with the results of the first significance 5 % with a correlation coefficient r = 0,715  Keywords: Kind of classroom ARCS, computer, linear algebra.